2008
DOI: 10.1002/elan.200804252
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of MWNTs/Au NPs/HS(CH2)6Fc Nanocomposite: Application to Electrochemical Determination of Ascorbic Acid

Abstract: In this article, a detailed electrochemical study of a novel 6-ferrocenylhexanethiol (HS(CH 2 ) 6 Fc) self-assembled multiwalled carbon nanotubes-Au nanoparticles (MWNTs/Au NPs) composite film was demonstrated. MWNTs/Au NPs were prepared by one-step in situ synthesis using linear polyethyleneimine (PEI) as bifunctionalizing agent. HS(CH 2 ) 6 Fc, which acted as the redox mediator, was self-assembled to MWNTs/Au NPs via Au-S bond. Transmission electron microscopy (TEM), energy-dispersive X-ray analysis (EDX), F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
0
9
0
3
Order By: Relevance
“…Study of the characteristics of the sensor by cyclic voltammetry showed a high sensitivity in the oxidation of ascorbic acid. The sensor was character ized by a reading time of approximately 3 s, stable readings, decreased oxidation potential of ascorbic acid, and relatively low detection limit for this compound [78].…”
Section: Sensors With Carbon Nanotubes Immobilized With Polyethyleniminementioning
confidence: 99%
“…Study of the characteristics of the sensor by cyclic voltammetry showed a high sensitivity in the oxidation of ascorbic acid. The sensor was character ized by a reading time of approximately 3 s, stable readings, decreased oxidation potential of ascorbic acid, and relatively low detection limit for this compound [78].…”
Section: Sensors With Carbon Nanotubes Immobilized With Polyethyleniminementioning
confidence: 99%
“…Представленные сведения позволяют сделать следующие выводы. Технологии изготовления электрохимических сенсоров путём нанесения углеродных нанотрубок на рабочую поверхность электрода с помощью полиэтиленимина [2][3][4][5][6][7], органических красителей [9,[11][12][13] и циклодекстринов [14][15][16][17] схожи между собой: нанотрубки распределяются в растворах перечисленных химических соединений, образуя гомогенную суспензию, которая далее наносится на поверхность электрода с последующим высыханием. Хитозан [18][19][20][21][22], белковые соединения [23,24], ионные жидкости [25,26], гели [27,28] и тиолы [29][30][31] также могут использоваться для нанесения углеродных нанотрубок на рабочую поверхность стеклоуглеродного, золотого или др.…”
Section: сенсоры с нанесением углеродных нанотрубокunclassified
“…Получаемые сенсоры позволяют определять большое число химических соединений, являющихся характерными для биомедицинских исследований, в частности дофамин [2-4, 11, 15, 19, 26, 43], допак [2,4], адреналин [4,15,35], норадреналин [4,17,20], аскорбиновая [2,7,19] и мочевая [16,20] кислоты, пероксид водорода [2,4,5,22,25,[27][28][29][36][37][38], NADH [21,44], глюкоза [2,21,22,28,29,[36][37][38][39]44], фруктоза [44], холестерин [27], цитохром с [30], амитрол [4,5], диурон [5], монурон [5], хлортолурон [5], офлоксацин [12], эстрадиол [13], тимин …”
Section: сенсоры с нанесением углеродных нанотрубокunclassified
See 1 more Smart Citation
“…Ferrocene and its derivatives, which are well-known substances as mediators due to their relatively low molecular mass, good electrochemical reversibility, regeneration at low potential, and high chemical stability, have been widely used to manufacture electrochemical sensor and biosensor [16][17][18]. However, there are several challenges concerning immobilization of electron-shuttling mediators on electrode surfaces, especially for soluble mediators with low molecular weight which can easily diffuse away from the electrode surface into the bulk solution, resulting in poor sensor response performance.…”
Section: Introductionmentioning
confidence: 99%